State of the world 2019: autocratization surges – resistance grows. Issue 6 (17th August 2020) - Maerz, Seraphine F.; Lührmann, Anna; Hellmeier, Sebastian; Grahn, Sandra; Lindberg, Staffan I.
ABSTRACT: This article analyses the state of democracy in the world in 2019. We demonstrate that the "third wave of autocratization" is accelerating and deepening. The dramatic loss of eight democracies in the last year sets a new record in the rate of breakdowns. Exemplifying this crisis is Hungary, now the EU's first ever authoritarian member state. Governmental assaults on civil society, freedom of expression, and the media are proliferating and becoming more severe. A new and disturbing trend is that the quality of elections is now also deteriorating in many countries. Nevertheless, there are also positive signs: pro-democracy protests reached an all-time high in 2019. People are taking to the streets to protest the erosion of democracies and challenge dictators. Popular protests have contributed to substantial democratization in 22 countries over the last ten years – including Armenia, Tunisia, and Ecuador. This was before the Covid-19 pandemic. Responses to the crisis, including many states of emergencies, risk further accelerating autocratization.